Study Of The Effectiveness Of Several Preservative Solutions On The Vase Life Of Cut Chrysanthemum Flowers (Chrysanthemum morifolium) var. Jayanti - Charissa Maria Simbawa; Langimanapa S. Demmassabu; Meity R. Rantung; Johannes E. X. Rogi; Bertje R. A. Sumayku; Yefta Pamandungan (Jurnal Agroekoteknologi Terapan, 2023)
This study aims to examine several preservative solutions for the vase life of cut flowers of chrysanthemum var. Jayanti. This research was conducted from January 2023 to February 2023 in the Wanea Urban Village, Wanea District, Manado City. This study used a completely randomized design (CRD) with 4 treatments of total, L1 (25 g/L Sugar + 1 mL/L Lime Juice + 1 mL/L Chlorox), L2 (40% Coconut Water + 25 g Sugar /L + Vinegar 0.4 mL/L + Chlorox 1 mL/L), L3 (25 g/L Sugar + 0.15 g/L Citric Acid + 250 g/L Basil Leaf Extract), and L4 (Coconut Water 40% + Saguer Vinegar 0.5 m/L + Betel Leaf Extract 250 g/L). Every treatment was repeated six times so that it would have 24 experimental units. In each of the experimental units, there are two samples, making a total of 48 units. Observational data were analyzed using Analysis of Variance (ANOVA) and continued with the Least Significant Different (LSD) test at the 5% level. The results showed that the composition of a solution of Sugar 25 g/L + Lime Juice 1 mL/L + Chlorox 1 mL/L was the most effective solution in maintaining the vase life of cut flowers of chrysanthemum var. Jayanti for 19,7 days. The composition of the best preservative solution with the addition of natural ingredients was obtained from the treatment of Sugar 25 g/L + Citric Acid 0.15 g/L + Basil Leaf Extract 250 g/L which could maintain the vase life of cut flowers of chrysanthemum var. Jayanti for 10,25 days. Keywords: Preservative Solutions, Cut Flowers, Chrysanthemum. Abstrak Penelitian ini bertujuan untuk mengkaji beberapa larutan pengawet untuk masa pajang bunga potong krisan var. Jayanti. Penelitian ini dilaksanakan pada bulan Januari 2023 sampai Februari 2023 di Kelurahan Wanea, Kecamatan Wanea, Kota Manado. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan 4 perlakuan yaitu, L1 (Gula Pasir 25 g/L + Air Jeruk Nipis 1 mL/L + Chlorox 1 mL/L), L2 (Air Kelapa 40% + Gula Pasir 25 g/L + Cuka 0,4 mL/L + Chlorox 1 mL/L), L3 (Gula Pasir 25 g/L + Asam Sitrat 0,15 g/L + Ekstrak Daun Kemangi 250 g/L), dan L4 (Air Kelapa 40% + Cuka Saguer 0,5 m/L + Ekstrak Daun Sirih 250 g/L). Setiap perlakuan diulang sebanyak 6 kali sehingga akan didapatkan 24 satuan percobaan. Dalam setiap satuan percobaan terdapat 2 sampel, sehingga total keseluruhan terdapat 48 unit percobaan. Data hasil pengamatan dianalisis dengan menggunakan Analisis Ragam (ANOVA) dan dilanjutkan dengan uji BNT pada taraf 5%. Hasil penelitian menunjukkan bahwa komposisi larutan Gula Pasir 25 g/L + Air Jeruk Nipis 1 mL/L + Chlorox 1 mL/L merupakan larutan yang paling efektif dalam mempertahankan masa pajang bunga potong krisan var. Jayanti selama 19,7 hari. Komposisi larutan pengawet dengan penambahan bahan alami terbaik didapatkan pada perlakuan Gula Pasir 25 g/L + Asam Sitrat 0,15 g/L + Ekstrak Daun Kemangi 250 g/L yang dapat mempertahankan masa pajang bunga potong krisan var. Jayanti selama 10,25 hari. Kata Kunci: Larutan Pengawet, Bunga Potong, Krisan